Representation in crisis and redefined citizenship in the aftermath of the 2012 Maribor protests - Toplak, Cirila (Teorija in praksa, 2017)
This article summarises the pertinent facts and analyses the outcomes of the 2012-2013 protests, in particular those in Maribor, with the aim of arguing that an acute crisis of representation was the principal reason for the popular discontent which was only exacerbated by the economic crisis, otherwise identified as the crucial context of the protests. Despite a post-protest relapse into neoliberal depoliticisation, a subsequent redefinition of post-democratic citizenship has emerged via innovative forms of direct action. The methodologies used to create this text were partly descriptive and critical analytical, and partly militant research which integrates scientific research with civic political activities.
Keywords: državljanstvo; kriza predstavništva; Maribor; Political representation; Politično predstavništvo; protesti; Slovenia; Slovenija